Manajemen Program Bimbingan Dan Konseling Di Ma Rohmatullah Cokro Magelang - Muhammad Najib Najib; Mungin Eddy Wibowo Wibowo; Heru Mugiarso (Didaktika Dwija Indria, 2026)
The increasing number of mental health problems among students requires the implementation of guidance and counseling (BK) programs that are managed systematically and sustainably. BK program management plays an important role in ensuring the effectiveness of services and supporting optimal student development. This study aims to analyze the management of the implementation of the guidance and counseling program, the evaluation process and managerial improvements, as well as supporting and inhibiting factors in its implementation at MA Rohmatullah Cokro Magelang. The study used a qualitative approach with a case study design. Data collection was conducted through interviews, observations, and documentation studies involving the principal and guidance and counseling teachers. Data analysis was carried out interactively through data reduction, data presentation, and drawing conclusions, with data validity testing using triangulation. The results of the study indicate that the management of the BK program has been implemented in a structured manner through the stages of needs analysis, planning, implementation, and evaluation. The program is designed based on student needs with a holistic approach oriented towards personal, social, learning, and career development. Program evaluations are conducted periodically and followed up to improve service quality. Supporting factors include the commitment of madrasah leaders, the competence of guidance and counseling teachers, and support for infrastructure, while inhibiting factors include limited service time and the ratio of guidance and counseling teachers to the number of students.